Image Based User Experience (UX) Factor Analysis- Mobile Phone Perspective - Morshed, Ishtiak; Shi, Huibin; Jafreen, Saujanna; Mostafa, Seraj Al Mahmud (International Journal of Computer Sciences and Engineering, 2018)
This paper mainly assesses original image used within a mobile application to understand the differences and comparing them with the standard size. The purpose is to predict success rate of mobile applications prior availability to its customer. To do so, we considered sizes of Android based application which can be improved for the ease of user friendliness. In android package kit (.apk) the buttons are usually (.png) files where the size may differ based on various screen perspective. An application is developed to find and compare the existing button size found in a mobile application to the respective standard in terms of User Experience (UX) factor. Initially, the result in this work will produce a statistic for developers to compare button standard with the original standard and finally produce a generic overview to get a probable success rate with other products in the market. The main finding of this work are, consider an agile based approach during development including revising the developed applications if required before the final release to their user and to overcome the standard of the design issue in terms of standard button measurements with similar products.